2008
DOI: 10.1177/0165025408093667
|View full text |Cite
|
Sign up to set email alerts
|

Who bullies whom? Social status asymmetries by victim gender

Abstract: This study asks whether bullies have higher social status than their victims. Social status was measured by social preference, popularity, and physical competence as perceived by children and teachers. A survey instrument was introduced to enable identification of specific victims associated with specific bullies. The sample was 508 fourth and fifth grade children from midwest U.S. elementary schools. Results indicated that peer- and teacher-perceived popularity were the optimal status measures for capturing h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
148
1
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 153 publications
(169 citation statements)
references
References 52 publications
11
148
1
9
Order By: Relevance
“…5 Those who are targeted by bullies are often physically weak, unassertive, or poor in understanding social cues 6 look different or are less popular than other peers. 7 Pediatric populations may be at increased risk 8 and three crosssectional studies reported that preterm children are more often bullied (victims) 9-11 whereas a fourth reported no differences. 12 Both, prematurity 13 and being bullied 4,5 predict emotional problems in adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…5 Those who are targeted by bullies are often physically weak, unassertive, or poor in understanding social cues 6 look different or are less popular than other peers. 7 Pediatric populations may be at increased risk 8 and three crosssectional studies reported that preterm children are more often bullied (victims) 9-11 whereas a fourth reported no differences. 12 Both, prematurity 13 and being bullied 4,5 predict emotional problems in adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, if adolescents perceive that their peers value aggressive behavior, they may intentionally use it to gain social status, constituting a mechanism for social adaptation. Whereas, in the realm of bullying, several studies have shown that bullying may serve as a way of positioning individuals in the peer social hierarchy (Dijkstra et al 2008;Olthof & Goosens, 2007;Rodkin & Berger, 2008). Bullies can be popular and socially central in their social groups (Rodkin et al, 2006).…”
Section: Aggression Bullying and Social Statusmentioning
confidence: 99%
“…Also, bullying and aggression are associated with social status (Cillessen & Mayeux, 2004;Rodkin & Berger, 2008). From this evidence it has been proposed that aggressive behaviors might be functional to achieve social status within the peer context (Berger & Rodkin, 2012;Ellis & Zarbatany, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Se utilizó el procedimiento de nominación de pares para establecer el grado de agresividad individual percibido por los pares. La nominación de pares es un procedimiento que ha sido utilizado anteriormente en muestras similares (Berger & Dijkstra, 2013;Rodkin & Berger, 2008), en que se solicita a cada participante marcar en una lista de su curso a los compañeras/os que en su opinión mejor calzan con una serie de descriptores. La agresividad incluye los siguientes ítems o descriptores: "comienza peleas", "se ríe de los otros", "se mete en problemas" e "ignora a los otros".…”
Section: Instrumentosunclassified
“…Se utilizó también el mismo procedimiento de nominación de pares para establecer el grado de prosocialidad individual percibido entre pares. Los ítems o descriptores de esta escala han sido utilizados en estudios anteriores (Berger & Dijkstra, 2013;Rodkin & Berger, 2008) y dan cuenta de manera adecuada de las conductas prosociales incluidas dentro de la dimensión de popularidad sociométrica (Dijkstra, Cillessen & Borch, 2013;Sandstrom & Cillessen, 2006), como son comprendidas en el contexto chileno. Los descriptores utilizados son: "es amable" y "coopera".…”
Section: Instrumentosunclassified